Temporal and spatial variation in distribution of fish environmental DNA in England's largest lake. Issue 1 (15th April 2019) - Lawson Handley, Lori; Read, Daniel S.; Winfield, Ian J.; Kimbell, Helen; Johnson, Harriet; Li, Jianlong; Hahn, Christoph; Blackman, Rosetta; Wilcox, Rose; Donnelly, Rob; Szitenberg, Amir; Hänfling, Bernd
Abstract: Environmental DNA offers great potential as a biodiversity monitoring tool. Previous work has demonstrated that eDNA metabarcoding provides reliable information for lake fish monitoring, but important questions remain about temporal and spatial repeatability, which is critical for understanding the ecology of eDNA and developing effective sampling strategies. Here, we carried out comprehensive spatial sampling of England's largest lake, Windermere, during summer and winter to (1) examine repeatability of the method, (2) compare eDNA results with contemporary gill‐net survey data, (3) test the hypothesis of greater spatial structure of eDNA in summer compared to winter due to differences in water mixing between seasons, and (4) compare the effectiveness of shore and offshore sampling for species detection. We find broad consistency between the results from three sampling events in terms of species detection and abundance, with eDNA detecting more species than established methods and being significantly correlated with rank abundance determined by long‐term data. As predicted, spatial structure was much greater in the summer, reflecting less mixing of eDNA than in the winter. For example Arctic charr, a deep‐water species, was only detected in deep, midlake samples in the summer, while littoral or benthic species such as minnow and stickleback were more frequently detected in shore samples. By contrast in winter, the eDNA of these species was more uniformly distributed. This has important implications for design of sampling campaigns, for example, deep‐water species could be missed and littoral/benthic species overrepresented by focusing exclusively on shoreline samples collected in the summer.